Optimization of hydroxyapatite synthesis from crab shell waste using response surface methodology (RSM) - Arnindi, Dinda Putri; Nisa, Assholihatun (Konversi, 2025)
Hydroxyapatite (HAp) is a bioceramic material widely used in biomedical applications due to its chemical similarity to the mineral component of human bone and teeth. This study aimed to optimize the synthesis of HAp from crab shell waste as a natural calcium source using the precipitation method combined with Response Surface Methodology (RSM). The main variables investigated were calcination temperature (800–1200°C) and Na₂H.PO₄ concentration (0,75–2,95 M), while pH was maintained at 11. The optimization results showed that both factors significantly affected the Ca/P ratio, which determines the stoichiometric quality of HAp formation. The optimum condition was obtained at a calcination temperature of 858,86°C and a Na₂HPO₄ concentration of 2,949 M, producing a Ca/P ratio of 1,67 with a desirability value of 1. Verification using Confidence Interval (CI), Tolerance Interval (TI), and Prediction Interval (PI) confirmed the model’s high accuracy and reliability. These findings demonstrate that crab shell waste can be effectively utilized as a sustainable calcium source for hydroxyapatite synthesis, offering environmental and economic benefits for future biomedical applications.